The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2147/dddt.s67592
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of S-1 chemotherapy in recurrent and metastatic nasopharyngeal carcinoma patients after failure of platinum-based chemotherapy: multi-institutional retrospective analysis

Abstract: PurposeThis retrospective study evaluates the efficacy and safety of S-1 chemotherapy for recurrent and metastatic nasopharyngeal carcinoma patients after failure of platinum-based chemotherapy.Patients and methodsThirty-nine patients with recurrent and metastatic nasopharyngeal carcinoma who failed previous platinum-based chemotherapy received oral S-1 chemotherapy (twice daily from day 1 to 14) every 3 weeks. The dose of S-1 was determined according to the body surface area (BSA): 40 mg twice a day for BSA <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…S-1 and capecitabine are two oral anticancer agents that may act as substitutes for 5-FU, with sufficient efficacy and relatively low toxicity profiles, offering an attractive choice for patients who have been significantly jeopardized by the complications caused by prior courses of palliative chemoradiotherapy. 25,26 Published data have proved their efficacy in various solid tumors, including NPC; [27][28][29][30][31][32][33][34][35][36][37][38] however, their utilization as maintenance therapy for mNPC has not been reported. Whether the use of these two oral agents in the maintenance phase could benefit mNPC patients who responded to previous systemic chemotherapy and radiotherapy remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…S-1 and capecitabine are two oral anticancer agents that may act as substitutes for 5-FU, with sufficient efficacy and relatively low toxicity profiles, offering an attractive choice for patients who have been significantly jeopardized by the complications caused by prior courses of palliative chemoradiotherapy. 25,26 Published data have proved their efficacy in various solid tumors, including NPC; [27][28][29][30][31][32][33][34][35][36][37][38] however, their utilization as maintenance therapy for mNPC has not been reported. Whether the use of these two oral agents in the maintenance phase could benefit mNPC patients who responded to previous systemic chemotherapy and radiotherapy remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…CDHP can enhance the efficacy and OXO can reduce the toxicity of tegafur, respectively. 13 , 14 Since inception, S-1 has been frequently used in gastrointestinal tumors. But more and more research has demonstrated that S-1 can provide significant effects on the survival rates in head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum drugs have been the most widely used chemotherapeutic drugs since they were put into clinical application in the 1970s [ 8 , 9 ]. Clinically, platinum drugs have been extensively used in the treatment of malignant tumors such as nasopharyngeal carcinoma [ 10 ], esophageal cancer [ 11 ], breast cancer [ 12 ], etc. Therefore, platinum drugs have become a symbol of an era among anticancer drugs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%